Unevenaged coppice holm oak stands: silvicultural description - Gonzalez, J. Mª.; Ibarz, P. (Forest Systems, 1998)
Uneven coppice stands of evergreen oak (Quercus ilex L.) of Gerona (NE Spain) are described. Three structurally different situations are analysed: close after silvicultural intervention, in the middle of two interventions and before cutting. Therefore 19 plots were selected in the area, obtaining dasometric and qualitative values in order to characterise traditional management. Positive tree selection of traditional management is proved, as well as a high percentage of trees of a good stem quality, particularly at dominant layer (33%). Liocourt constant values in these stands were determined: they change for every described situation (2.8-1.6; 1.2-2.6; 1.7-2.8). With these values, 45 types of uneven evergreen oak forests were modelized modifying initial density (900, 1100 and 1200 stems/ha) and q values (DC10: 2.5; 2.7; 2.8; DC>15: 1.5; 1.6; 1.7; 1.8; 1.9), while keeping maximum initial diameter (25 cm) and rotation (30 years). The comparison between these models don’t show significant differences independent from initial values. Using mean values obtained from the sample plots, a preliminary optimal equilibrium curve for uneven oak-coppice stands has been developed. Finally structural differences between those stands, traditional ones of Central Europe and uneven Pinus nigra forests of Pyrenees are upbright.